2018
DOI: 10.33549/physiolres.933831
|View full text |Cite
|
Sign up to set email alerts
|

Serum HMGB1 Levels and Its Association With Endothelial Dysfunction in Patients With Polycystic Ovary Syndrome

Abstract: High-mobility group box 1 (HMGB1) is newly discovered protein, which play a crucial role in the pathogenesis of systemic inflammation. Recent studies showed that HMGB1 is one of the important pathophysiological mechanisms in the occurrence and development of atherosclerosis. The purpose of the present study was to investigate the relationship between serum HMGB1 levels and endothelial function in patients with polycystic ovary syndrome (PCOS). Eighty newly diagnosed patients with PCOS and eighty normal women o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Several studies, including this study (Figure 8), have confirmed that the serum level of HMGB1 is higher in PCOS [18], suggesting that inhibiting HMGB1 could be a reliable therapeutic approach against PCOS. Glycyrrhizin, a drug believed to be safe for human use, can directly bind to and inhibit HMGB1 [40].…”
Section: Discussionsupporting
confidence: 64%
“…Several studies, including this study (Figure 8), have confirmed that the serum level of HMGB1 is higher in PCOS [18], suggesting that inhibiting HMGB1 could be a reliable therapeutic approach against PCOS. Glycyrrhizin, a drug believed to be safe for human use, can directly bind to and inhibit HMGB1 [40].…”
Section: Discussionsupporting
confidence: 64%
“…In this study, we show that in addition to decreased AR protein abundance (this study and [48]) and increased fetal survival in pregnant PCOS‐like rats [48], treatment with the AR antagonist flutamide also decreased HMGB1, TLR2, TLR4 and NFκB p65 protein levels in the gravid uterus with viable fetuses. It has been reported that compared to women without PCOS, the levels of HMGB1 mRNA and protein are significantly increased in both ovarian granulosa cells [33–36], endometrium (in this study), follicular fluid [35] and serum [36–39] in women with PCOS. While the actions of HMGB1‐induced inflammation are mediated by binding to TLRs [22,23], we show here that uterine HMGB1 and TLR2/4 protein levels are positively correlated with each other in pregnant PCOS‐like rats.…”
Section: Discussionmentioning
confidence: 63%
“…FMD improved in three (27%) out of 11 study-groups; ET-1 levels did not improve in one study where this was assessed; whilst IMT improved in three (33%), but deteriorated in one out of nine study groups (Table 2). 15,35,44,57,58,63,68,77,86,87,91,96,101, Similarly, CRP levels were not reduced in all four study groups that assessed it. A meta-analysis including three randomized controlled studies that compared oral contraceptives containing oestrogen (ethinylestradiol) with progestogen drospirenone or chlormadinone acetate, showed a beneficial effect of ethinylestradiol/drospirenone over ethinylestradiol/chlormadinone acetate in reducing androstenedione levels and total testosterone after 3 months, and Ferriman-Gallwey score after 6 months.…”
Section: Oral Contraceptive Pillsmentioning
confidence: 88%
“…CRP levels were not reduced in five out of six (83%) studies, 35,63,77,86,116 not confirming the documented anti-inflammatory action of metformin on this low-grade inflammation present in this young population. 35,63,77,86,101,117 Thiazolidinediones Thiazolidinediones include three drugs: troglitazone, rosiglitazone and pioglitazone. They act by enhancing glucose uptake in adipose and muscle tissues.…”
Section: Metforminmentioning
confidence: 99%